Molecular, morphological and ecological studies of Limnospira platensis (Cyanobacteria), from saline and alkaline lakes, Pantanal Biome, Brazil - Santos, Kleber Renan de Souza; Hentschke, Guilherme Scotta; Ferrari, Graciela; Andreote, Ana Paula Dini; Fiore, Marli de Fátima; Vasconcelos, Vitor; Sant’Anna, Célia Leite (Frontiers in Environmental Science, 2023)
We studied nineteen populations of A. platensis (Microcoleaceae, Cyanobacteria), from Pantanal (Brazil) shallow, saline and alkaline lakes. The lakes are connected to the Paraná and Paraguay Rivers Basins, and during wet seasons, and the waters flow towards La Plata River estuary. Morphology of natural populations and cultures were analyzed using optical microscope, and 16S rDNA sequences were used for the BI and ML phylogenetic analysis. The morphological analysis shows that our populations fit in the original description of A. platensis, but with additional aerotopes. Also, it is evident that these structures are facultative and the species is planktonic, rather than benthic without aerotopes, as originally described. The phylogenetic analysis shows our strains in the monophyletic Limnospira clade. Considering that, in this paper we transfer the species A. platensis to the genus Limnospira, based on phylogenetic and morphological data. This new taxonomical combination is supported also by ecological data, and indicates that the species is more related and abundant in Pantanal, than in La Plata Basin, region from where it was originally described. According to our results, L. platensis is planktonic or benthic and typical from saline, alkaline and warm waters.